The Phenomenon of Cancel Culture as a Response to Legal Dysfunction Between Social Control or Moral Destruction? - Lubis, Mhd. Yade Rafli (Journal of Sumatera Sociological Indicators, 2025)
The cancel culture phenomenon emerged as society's response to legal dysfunction which is no longer able to provide substantive justice. This research aims to understand how cancel culture acts as an alternative social control mechanism amidst weakening legal institutions. By using literature study methods and the Durkheim approach, this research found that cancel culture has two sides: as a form of progressive public participation, as well as the potential for moral destruction due to judgments that are not based on ethics. Digital space has become a forum for people to express dissatisfaction with the legal system, but it also creates new risks in the form of symbolic violence. Therefore, cancel culture is understood as an ambivalent social phenomenon that reflects the need for legal reform and strengthening digital ethical awareness.